Psychological flow and its relationship to visual focus and crushing skill accuracy of volleyball - Naji Hussein, Hasanain (International Journal of Psychosocial Rehabilitation, 2020)
The current study was conducted in order to find the relationship between psychological flow, visual focus, and the accuracy of the crushing skill of volleyball, as the researcher used the descriptive approach in the manner of correlations. Their number is (35) players. (5) players from the main sample were excluded. They participated in the exploratory experiment. (2) players were excluded due to injury. (12) players were chosen randomly to represent the main sample of the experiment. To achieve the objectives of the research, the researcher adopted the psychological flow scale and the visual focus test. According to the tests of the computerized Vienna system of the Austrian Schofred Company and the crushing hitting test with volleyball, which are standardized tests and applied to the Iraqi environment, and after processing the data statistically, the researcher concluded that there is a significant correlation between psychological flow, visual focus, and the accuracy of the crushing hitting skill with volleyball, and that the research sample enjoys psychological flow and self-awareness As a result of the interest in the psychological aspect of the players and the regular training of psychological skills, and that the use of measurement and testing methods a Modern and computerized has a positive role in obtaining accurate measurement results..